2022
DOI: 10.3389/fmicb.2022.754995
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas12a Technology Combined With RPA for Rapid and Portable SFTSV Detection

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is a new tick-borne pathogen that can cause severe hemorrhagic fever. Fever with thrombocytopenia syndrome caused by SFTSV is a new infectious disease that has posed a great threat to public health. Therefore, a fast, sensitive, low-cost, and field-deployable detection method for diagnosing SFTSV is essential for virus surveillance and control. In this study, we developed a rapid, highly sensitive, instrument-flexible SFTSV detection method that utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Unlike the conventional nucleic acid detection methods, our CRISPR/Cas-based methods for SFTSV involve a substantially shorter operation time and avoid the need for thermal circulation apparatus. The whole detection process was easily conducted at 37°C within 1 h. Until now, the Cas12a-based detection method for SFTSV has been reported and similar work was carried out in this study ( Huang et al, 2022 ). Moreover, we first proposed the detection method based on CRISPR/Cas13a for SFTSV, and the lowest detection limit was 0.75 cp/μl.…”
Section: Discussionmentioning
confidence: 76%
“…Unlike the conventional nucleic acid detection methods, our CRISPR/Cas-based methods for SFTSV involve a substantially shorter operation time and avoid the need for thermal circulation apparatus. The whole detection process was easily conducted at 37°C within 1 h. Until now, the Cas12a-based detection method for SFTSV has been reported and similar work was carried out in this study ( Huang et al, 2022 ). Moreover, we first proposed the detection method based on CRISPR/Cas13a for SFTSV, and the lowest detection limit was 0.75 cp/μl.…”
Section: Discussionmentioning
confidence: 76%
“…The results showed that SFTSV viral load and NLR had higher AUC, sensitivity, and specificity, which indicated that SFTSV viral load and NLR were better than the other three indicators in predicting the incidence of fatal outcomes. The importance of the detection of SFTSV viral load had been repeatedly mentioned in previous studies (Huang et al, 2022 ). It is worth mentioning that only 143 patients among the enrolled 228 patients with SFTS had accepted SFTS viral load test in this study.…”
Section: Discussionmentioning
confidence: 77%
“…After reading the full text of the articles, 103 were discarded, including 48 that did not use clinical patient samples or lacked data, 35 that were not on nucleic acid‐related diagnostic techniques, 14 that lacked reference standards, and 6 that were not on or related to SFTS. A final total of 16 articles were included, seven on RT‐PCR 19 , 20 , 24 , 25 , 26 , 27 , 28 and seven on RT‐LAMP, 16 , 21 , 29 , 30 , 31 , 32 , 33 and two that were on both RT‐PCR and RT‐LAMP. 15 , 34 A flowchart of the research process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%